THE RELATIONSHIP BETWEEN SELF-ESTEEM AND RESILIENCE IN PRISONERS IN CORRECTIONAL INSTITUTIONS FEMALE CLASS II B PADANG - Husen, nurul; Aulia, Fara (Causalita, 2024)
Correctional institutions are institutions used to train and guide law violators. Inmates during their prison period experience problems such as inner conflict, trauma, difficulty adapting, unstable emotions and anxiety. To be able to survive and adapt during the prison period inmates need the ability to adapt and overcome various problems that arise which are made with resilience, one of the factors that affect a person's resilience is self-esteem. Therefore, this study aims to see the relationship between self-esteem and resilience in female inmates of class IIB Padang. This study uses a quantitative research method with a correlational approach. The number of samples in this study was 53 inmates who were selected using purposive sampling techniques. Data collection was carried out using the resilience scale and self-esteem scale from Karimah (2022). The data analysis in this study uses product moment correlation analysis with the help of SPSS.26. The results of this study show that self-esteem has a relationship with resilience in inmates in class IIB Padang women's correctional institution.